Preventing Premature Deindustrialization in Sub-Saharan Africa: The Importance of the Road Transportation Sector - sparks, donald (Advances in Social Sciences Research Journal, 2016)
Since independence in the early 1960s the countries of sub-Saharan Africa have generally viewed industrialization as an essential ingredient of economic development. Indeed, most of the world’s advanced nations are often grouped as the “industrial economies” and the progression from agriculture-based economies to manufacturing and service-based ones has been seen as key to development strategy. However, there is a growing literature that suggest that this path is no longer one that can necessarily be followed. Indeed, there is strong evidence that for many countries deindustrialization is actually the problem. Infrastructure will need to play an even great role if the region is to successfully industrialize and meet its development targets. Of course roads form only a part of transportation infrastructure in African countries --albeit the most important part, as road transport accounts for 85% of the region’s passenger and freight and is the only form of access to most rural communities where 65% of the population live. For the region to develop it must continue on its path of economic and political reform, but at the same time it must look at improving its basic infrastructure, especially good roads and find new means for increased mobility for the majority. Improved road infrastructure is vital if Africa is to escape the scourge of deindustrialization. This paper examines the phenomenon of deindustrialization and see how improved road transport might roll back that decline.